Preliminary results on microplastic pollution from agricultural soil in Vietnam: Distribution, characterization, and ecological risk assessment - Oanh Doan, Thi; Thuy Duong, Thi; My Nguyen, Thi; Quynh Hoang, Thi; Tam Luong, Thanh; Thao Pham, Phuong; Thanh Nga Cao, Thi; Thu Le, Phuong; Hieu Phung, Hieu Phung; Phuong Quynh Le, Thi; Mai Anh Dang, Thi; Thuy Bui, Phuong; et al. (Vietnam Journal of Earth Sciences, 2023)
Microplastics (MPs) have been extensively studied in aquatic systems; however, their presence in general agricultural systems and in particular, soil still needs comprehensive understanding. This study conducted a field survey at 25 sites to investigate the abundance of MPs in agricultural soil. The MPs in these soil samples were separated using sieves and filters by the density separation method with NaCl solution (d = 1.2 g/cm3). The density of MPs in agricultural soils ranged from 1,700 items/kg to 38,800 items/kg, with an average of 11,716 ±10,726 items/kg. The black-colored MPs were found to be dominant, followed by white, purple, red, and blue. The fibers represented most of the MPs' shapes observed in this research (77.9±17.4%). MPs in agricultural soil samples were tiny particles with sizes of <1,000 µm and 1,000-2,000 µm. A significant difference was observed  in the concentration of MPs in locations near and far from residential areas and manufacturing facilities. The average concentration of MPs in the soils adjacent to the residential and manufacturing facilities and near the agricultural solid waste collection sites  was 21,471±12,729 items/kg and 20,188±4,403 items/kg, much higher than in distant these locations at 4,418±1,573 items/kg. These results suggest that domestic, industrial, and agricultural activities could contribute to MP pollution in agricultural soil. The ecological dangers MPs pose in terrestrial and aquatic environments have drawn much attention from the scientific community. This work represented the first effort to comprehend the ecological risk of MPs on selected samples of Vietnamese agricultural soil. According to the Pollution Load Index (PLI) values, most agricultural soil samples in this study were contaminated with MPs at hazard level IV. The potential ecological risk index (PERI) values of agricultural soil samples from nearby residential, industrial, or agricultural solid waste areas indicated a higher ecological risk.